PENGARUH PENEMPATAN DAN STRES KERJA TERHADAP KEPUSAN KERJA KARYAWAN PADA AGUNG PUTRA APARTMENT BALI - Muliani, Ni Made; Indrawati, Ayu Desi (E-Jurnal Manajemen; Vol 5 No 9 (2016), 2016)
Human resource is the most important factor in an organization or company to achieve efficiency and effectiveness in conducting its business. The purpose of this study was to examine the effect of the placement and job stress on employee job satisfaction. This research was conducted in Agung Putra (AP) Apartment Bali with a number of research respondents as many as 40 employees. The analysis technique used is multiple linear regression. Based on the results of research conducted concluded that placement sigifikan positive effect on job satisfaction and job stress a significant negative effect on employee job satisfaction. Suggested to leader Agung Putra Apartment Bali to be more selective in looking at employees' work experience, able to disseminate the various forms of organizational changes, taking into account danlebih reward or remuneration in accordance with the calculation of the workload of employees.
Keywords: placement, job stress, job satisfaction